2021
DOI: 10.1007/s10072-021-05329-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on chronic migraine treated with erenumab: a case report

Abstract: Background Headache is a frequent symptom of the novel coronavirus 19 disease . To date, there are limited information on how COVID-19 affects migraine and its treatment. Case description A 47-year-old patient, suffering from chronic migraine and medication-overuse headache, in September 2020 started erenumab at 70 mg once monthly. Two months later, monthly migraine days decreased from 20 to 5. On the third month, the patient developed mild COVID-19 symptoms, experiencing extreme fatigue, hyposmia, and attenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…The increased severity was noted to be significantly higher with elder subjects. In agreement, Grassini et al ( Grassini et al, 2021 ), Arca and Starling ( Arca and Starling 2020 ) reported a significant exacerbation of headache attacks during COVID-19 infection in a previous case report. Patients, on the other hand, developed pneumonia and reported various clinical symptoms suggestive of SARS-CoV-2-related meningoencephalitis.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The increased severity was noted to be significantly higher with elder subjects. In agreement, Grassini et al ( Grassini et al, 2021 ), Arca and Starling ( Arca and Starling 2020 ) reported a significant exacerbation of headache attacks during COVID-19 infection in a previous case report. Patients, on the other hand, developed pneumonia and reported various clinical symptoms suggestive of SARS-CoV-2-related meningoencephalitis.…”
Section: Discussionsupporting
confidence: 78%
“…Meningoencephalitis caused by a viral agent directly invading the brain, metabolic encephalopathy, and cytokine release syndrome are all possible explanations. (CRS), ( Arca and Starling, 2020 , Grassini et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 symptoms are more severe and mortality rates are higher in aged human patients, adding significance to our results. Further, two relatively recent case studies showed that increased headaches after SARS-CoV-2 infection can be treated with CGRP monoclonal antibodies (Grassini et al 2021; Ozkan et al 2022). Our study suggests that olcegepant or other CGRP treatments may be further explored particularly to treat headaches or migraines in aged individuals and/or those with high IL-6 levels upon COVID-19 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Single reports on effectiveness without adverse events cover the exposure to Erenumab in the first 2 weeks of pregnancy [109], during breast feeding [113], and in myasthenia gravis treated with immunoglobulins [123]. In one patient each, Erenumab and fremanenzumab were effective in COVID-19-related migraine exacerbations [106,112] and in two patients use of rimegepant during treatment with Erenumab was found effective and well tolerated [122]. Notably, no recommendation concerning the safety in these conditions can be given based on this anecdotal evidence.…”
Section: Deterioration Of Preexisting Disordermentioning
confidence: 99%